2022
DOI: 10.1021/acs.jafc.2c07026
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Formation of 2,3-Butanedione and Pyrazines through Intervention of Added Cysteine during Thermal Processing of Alanine-Xylose Amadori Compounds

Abstract: The intervention of cysteine (Cys) on the formation of 2,3-butanedione and pyrazines was evaluated during the thermal processing of the alanine-xylose Amadori compound (AX-ARP). With the involvement of Cys, the competitive formation of 2,3-butanedione and pyrazines was induced. The formation of 2,3-butanedione in the AX-ARP/Cys model was suppressed due to the inhibitory effect of the precursors of 2,3-butanedione like deoxypentosones, while the added Cys in the AX-ARP/Cys model competed with the recovered alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…When purified ARP was heated alone, as mentioned above, the content of pyrazines was not detected or it was in a very minute amount, but with the addition of Cys, the formation of pyrazines was detected at pH 7 and above (Table ), which was consistent with the study of Shu et al They suggested that the amino group of Cys was more reactive at pH 7.1 to form pyrazines in the 2,5-dimethyl-4-hydroxy-3­(2H)-furanone and Cys reaction system. It was observed that the content of pyrazines in the presence of Cys was higher than that formed from the ARP heated alone (Table ), which was due to the fact that Cys could compete with the regenerated alanine to capture α-dicarbonyl compounds leading to the increase of pyrazines . In addition, Cys could undergo thermal degradation to release ammonia, which subsequently could react with some reactive intermediates such as glycolaldehyde generated from the degradation of ARP to form more α-aminoketones, and thus promote the formation of pyrazines .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When purified ARP was heated alone, as mentioned above, the content of pyrazines was not detected or it was in a very minute amount, but with the addition of Cys, the formation of pyrazines was detected at pH 7 and above (Table ), which was consistent with the study of Shu et al They suggested that the amino group of Cys was more reactive at pH 7.1 to form pyrazines in the 2,5-dimethyl-4-hydroxy-3­(2H)-furanone and Cys reaction system. It was observed that the content of pyrazines in the presence of Cys was higher than that formed from the ARP heated alone (Table ), which was due to the fact that Cys could compete with the regenerated alanine to capture α-dicarbonyl compounds leading to the increase of pyrazines . In addition, Cys could undergo thermal degradation to release ammonia, which subsequently could react with some reactive intermediates such as glycolaldehyde generated from the degradation of ARP to form more α-aminoketones, and thus promote the formation of pyrazines .…”
Section: Resultsmentioning
confidence: 99%
“…Volatile compounds were identified by comparing their retention indices (RI) relative to n -alkane (C 7 –C 30 ) standards under identical GC–MS conditions with KI values obtained from the NIST database. The volatile substances detected in different systems were quantified according to the previous study . Different concentrations of the chemical standards and the fixed concentration of internal standards were mixed to construct standard curves.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations